2015
DOI: 10.1177/1012690215616271
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between the relative age effect and leadership behaviors among male ice hockey players

Abstract: This study examined the role of relative age on leadership behaviors among male house league ice hockey players. Athletes completed an online survey that solicited their birthdate along with their responses to the leadership scale for sport. As expected, the results of our analyses revealed no relative age effects. Captains scored significantly higher on the training and instruction, democratic behavior and social support dimensions of the leadership scale for sport. While there were significant multivariate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 55 publications
(107 reference statements)
4
10
0
2
Order By: Relevance
“…Outside of sport, relatively older high school students have been found to hold leadership roles more often and obtain more leadership experience prior to graduation (Dhuey & Lipscomb, 2008). In light of the current findings and the similar results of Chittle, Horton, Weir, and Dixon (2015) it appears that relatively younger and older hockey players demonstrate similar leadership behaviors, possibly due to their participation in house league sport. If sport provides opportunities that are transferrable to other life contexts, the impact of relative age may diminish.…”
Section: Discussionsupporting
confidence: 62%
“…Outside of sport, relatively older high school students have been found to hold leadership roles more often and obtain more leadership experience prior to graduation (Dhuey & Lipscomb, 2008). In light of the current findings and the similar results of Chittle, Horton, Weir, and Dixon (2015) it appears that relatively younger and older hockey players demonstrate similar leadership behaviors, possibly due to their participation in house league sport. If sport provides opportunities that are transferrable to other life contexts, the impact of relative age may diminish.…”
Section: Discussionsupporting
confidence: 62%
“…Given that prior education research suggested that relative age may impact leadership opportunities (Dhuey & Lipscomb, 2008), we anticipated that the relatively youngest may be less likely to display leadership behaviors, particularly in sports where RAEs have been common. However, we found that the frequency with which athletes engage in specific Note: Wilks' Lambda = 0.943, X 2 (5) = 13.982, p = 0.016; * significantly discriminated between formal and informal leaders leadership behaviors did not differ across quartile of birth, which aligns with the research conducted on male travel and house league players (Chittle et al, 2017;Chittle et al, 2017a). Failing to reject the null hypothesis may be a positive finding as it suggests that relative age may not be impacting athlete leadership engagement.…”
Section: Discussionsupporting
confidence: 85%
“…To the best of our knowledge, there have only been two prior studies that have examined the influence of relative age on the leadership behaviors of athletes, with these projects targeting male ice hockey players (Chittle, Horton, & Dixon, 2017;Chittle, Horton, Weir, & Dixon, 2017a). Chittle et al (2017a) examined house league male ice hockey players and found no significant differences in leadership behaviors across birth quartiles. Similarly, for competitive male ice hockey players, relative age did not appear to influence the frequency with which they exhibited leadership behaviors (Chittle et al, 2017).…”
Section: Raes and Leadershipmentioning
confidence: 99%
See 2 more Smart Citations